Étude Rétrospective Des Atteintes Rénales Toxiques Medicamenteuses Au Centre Hospitalier Universitaire De Yaoundé (2009-2014) - Nkoyock, Emilienne Grâce; Yongsi, Blaise H. Nguendo; Ndié, Justin; Ateba, Patrice Emmanuel Awono (European Scientific Journal, ESJ, 2016)
Background: Renal drug toxicity are affections that attacking the renal parenchyma as a result of the consumption of drug substance. In Cameroon, anarchic consumption of medicinal drug subsequent of a growth in unauthorised sales drug increase the risk of developing these pathologies. Objective: This study aims at describing and laying the epidemiological profile of drug-induced toxic renal diseases in Yaoundé University Teaching Hospital over the last 6 years (2009 – 2014). Materials and methods: A retrospective cross-sectional study was carried out from the 1st of July to the 30th of November 2015, at the polyvalent reanimation service and the haemodialysis unit of the Yaoundé University Teaching Hospital. With the aid of a questionnaire, the files of patients consulted and hospitalised in these services over a period of 6 years (1st January 2009 to 31st December 2014) were examined. Included in this study, patients suffering from renal drug toxicity. The data input, treatment and analysis were carried out with the help of Epi Info 7 and SPSS 22 software. Results: Forty-four (44) cases renal drug diseases representing 18.3% of the 240 files examined were noted. The average age of the patients was 48±18 years and varied between 11 and 87 years. The male sex constituted the majority of the suffers cases with a sex ratio of 2.67 (M/F). Acute renal infections with frequency of 65.9%, were most dominant of drug affections. Traditions concoctions (50%), gentamycin (11.4%) and paracetamol (9.1%) were the most incriminating drug in the occurrence of these renal drug affecting. The evolution was noted by a 43% complete recovery against a 14% death. Conclusion: Renal drug toxicities represent a non-negligible proportion of the renal affection ailments in the specialised centres like Yaoundé University Teaching Hospital. The elaboration and putting into action a sensitization plan for populations on the proves necessary, as this would help improve pharmacovigilance and also reduce the consumption of illicit drugs to a greater extent responsible for renal problems.